A Survey on Advanced Algorithms in Topic Modeling - Padmaja, Padmaja Ch V R; Lakshmi Narayana, S; Divakar, Ch (International Journal of Computer Sciences and Engineering, 2025)
In this paper, Survey of various topic modeling algorithms is presented. Introduced classification differs from earlier efforts, providing a complementary view of the field. This survey provides a brief overview of the existing probabilistic topic models and gives motivation for future research.